Zara’s brand perception: a comparative approach between Brazil and Spain - Pretti, Nelson (2018)
In this study, the author analyses the effects of country of origin and brand positioning on consumer’s brand perception and purchase intention of the brand ZARA. For the analysis, the author uses online survey to collect data from students in Spain and in Brazil. ZARA’s brand perception and purchase intention were expected to be higher in Brazil, but the results suggest that ZARA has an equal or even better performance in Spain than in Brazil. Although the results provide a strong evidence of a Brazilian preference for nonlocal brands, this preference hasn’t provided the expected positive results on the other variables analysed. A deeper analysis of the correlations among the variables brought light to some aspects, but, due to the limitations of the thesis’ scope, the data collected didn’t allow a full comprehension of all the causes behind the results found.